Using a 3D printer in cardiac valve surgery: a systematic review - Boll,Liliana Fortini Cavalheiro (2019)
SUMMARY BACKGROUND: The use of the 3D printer in complex cardiac surgery planning. OBJECTIVES: To analyze the use and benefits of 3D printing in heart valve surgery through a systematic review of the literature. METHODS: This systematic review was reported following the Preferred Reporting Items for Systematic Review and registered in the Prospero (International Prospective Register of Systematic Reviews) database under the number CRD42017059034. We used the following databases: PubMed, EMBASE, Scopus, Web of Science and Lilacs. We included articles about the keywords “Heart Valves”, “Heart Valve Prosthesis Implantation”, “Heart Valve Prosthesis”, “Printing, Three-Dimensional”, and related entry terms. Two reviewers independently conducted data extraction and a third reviewer solved disagreements. All tables used for data extraction are available at a separate website. We used the Cochrane Collaboration tool to assess the risk of bias of the studies included. RESULTS: We identified 301 articles and 13 case reports and case series that met the inclusion criteria. Our studies included 34 patients aged from 3 months to 94 years. CONCLUSIONS: Up to the present time, there are no studies including a considerable number of patients. A 3D-printed model produced based on the patient enables the surgeon to plan the surgical procedure and choose the best material, size, format, and thickness to be used. This planning leads to reduced surgery time, exposure, and consequently, lower risk of infection.